Analisis Faktor-Faktor yang Mempengaruhi Kondisi Financial istress Suatu Perusahaan yang Terdaftar di Bursa Efek Jakarta - Luciana Spica Almilia (The Indonesian Journal of Accounting Research, 2013)
There is abundant researches describing prediction models of firm’s bankruptcy, but only few researches have sought to predict firm’s financial distress. The financial distress condition happens before bankruptcy. The purpose of this research is to examine the factors that affect financial distress condition of a firm. The factors that are examined on this research are financial ratio, industry relative ratio, firm’s sensitivity to macroeconomic variables, auditor reputation and underwriter reputation.The sample consists of 19 companies which  were delisted from 1999 through 2002 and 41 listed companies until 2002. The sample are selected using purposive sampling approach. The statistic method which is used to test on the research hypothesis is logistic regression. Backward stepwise technique is used to gain a model that has the highest classification power, by removing the most insignificant variable in the model.The results show that industry relative ratio has a higher classification power rather than unadjusted financial ratio. This research also indicates that a firm’s sensitivity to macroeconomic variables (IHSG, General Consumer Price Index, Money supply and SBI interest rates) and auditor reputation is a significant variable in determining of companies’ financial distress.